Stand up straight! : a history of posture - Gilman, Sander L. (Reaktion Books, 2018)
Our bodies change over time; posture is ambiguous in a number of cultural and disciplinary realms. Your posture can denote you as healthy or ill, elegant or slovenly, beautiful or ugly. Gilman examines the history and sociology of posture: how society views who we are and what we are able to do by how our bodies appear. -- adapted from jacket and preface.